A Comparison of Students' Perceptions of Chemistry Learning via Google Classroom, E-Learning Madrasah, and Discord - Anggraeni, Egi Syahrah; Rindoi, Muhamad; Saputri, Deveronica Karning; Prasiwi, Dinar; Lestari, Sri; Sukemi, Sukemi (Journal of Educational Sciences, 2025)
Online learning non face-to-face interaction can be effectively supported by learning management systems (LMS) such as Google Classroom, E-learning Madrasah, and Discord. This study aims to determine the differences in students' perceptions about chemistry learning via Google Classroom, E-learning Madrasah, and Discord. The perceptions measured include aspects of ease of access, benefits, communication and interaction, instruction delivery, and student satisfaction. This research is a retrospective comparative quantitative study, involving 68 students from SMAN 2 Samarinda (Google Classroom), 73 students from MAN 1 Samarinda (E-Learning Madrasah), and 74 students from SMAN 13 Samarinda (Discord) as sample. Data were collected via documentation and analyzed used the Kruskal-Wallis and Dunn's Post-hoc tests. The Kruskal-Wallis test revealed a significant difference in perceptions (0.003<0.05). Dunn’s post-hoc analysis indicated significant differences between Google Classroom and E-Learning Madrasah (sig. <0.001) and between Google Classroom and Discord (sig. 0.041), but there was no significant difference between E-learning Madrasah and Discord. Overall, students' perceptions of chemistry learning using Google Classroom were better than using E-learning Madrasah and Discord.